Tylothrips Bruesi, A New Thysanopteron From Florida - J. Douglas Hood (Psyche: A Journal of Entomology)
The following species was taken within a few miles of Professor Charles T. Brues' home on the St. Johns River, in Florida, shortly after we had collected together and renewed an acquaintance which apparently began very nearly fifty years ago, long before he became Professor of Entomology at Harvard University and Editor of Psyche.